Exploring the Use of Web 2.0 Tools in Academic Environments: A Case Study of North Campus Colleges, University of Delhi (LIS TODAY, 2025)
This study examines the adoption of Web 2.0 tools among colleges in the North  Campus of the University of Delhi, highlighting their role in fostering digital  engagement and academic outreach. Analyzing 14 colleges and 42 Web 2.0 tools,  the study reveals that platforms such as X (formerly Twitter), Facebook, Instagram,  YouTube, and LinkedIn are the most widely utilized. Hansraj College, Indraprastha  College for Women, Kirori Mal College, and the School of Open Learning emerged  as leaders in digital adoption, each employing five tools, while St. Stephen’s College  and Shaheed Sukhdev College of Business Studies showed no usage. X leads as the  most-used platform, with 23.81% adoption, followed by Facebook and Instagram  at 21.43% each. YouTube and LinkedIn play significant roles in video content  sharing and professional networking. However, niche tools like Google Play and  TinyURL show minimal adoption. The study also highlights disparities in YouTube  engagement, with Kirori Mal College achieving the highest subscriber count and  video content output. Findings emphasize the importance of structured digital  strategies to enhance outreach, institutional branding, and stakeholder interaction.  Recommendations include broader adoption of underutilized tools, training for  faculty and staff, and leveraging analytics to optimize engagement. This research  underscores the transformative potential of Web 2.0 in academic environments.
Keywords: Web2.0 toolsd; Higher Education; Academic Environments; North Campus; Colleges; University of Delhi